Sufi education and its goals - BENAMAR, Samia (Social Sciences Journal)
The seeds of Sufism appeared in the sky of Islamic thought at the beginning of the second century AH in the form of severe tendencies of asceticism in the enjoyment and adornment of the world, as a result of the sins committed by the disobedient Muslim and his attempt to erase them by asking for forgiveness from his Lord, as well as the extreme terror that befell the disobedient from the Last Day and what There is severe torment in it, which makes them ask for repentance from their creation and asceticism in life, and from here Sufism means commitment to a path in life that enables them to reach a relationship with God.